Chvalaea yolkamini sp. nov. (Diptera: Hybotidae), the first Mexican species of genus discovered on Instagram - Jaume-Schinkel, Santiago; Soares, Matheus M.m.; Barros, Luana M. (Zootaxa, 2020)
A new species of Chvalaea Papp & Földvári, 2002 is discovered after a photo on a social network and later collected in nature. Chvalaea yolkamini sp. nov. is described and illustrated here. In addition, for the first time we describe eggs with scanning electron microscopy and report on adult hunting behavior.